Pengaruh Literasi Keuangan, Inovasi Produk dan Inklusi Keuangan terhadap Kinerja Keuangan Umkm Kuliner: Studi Kasus Pada UMKM Kuliner di Alun-alun Kidul Kota Surakarta - Devi Citra Oktavia; Suprihatmi Suprihatmi; Ririn Indriastuti (Pusat Riset dan Inovasi Nasional, 2026)
Small and medium enterprises (SMEs) are one sector that contributes to the economic growth of a country or region by creating new jobs. One such sector is the culinary MSMEs in Alun-Alun Kidul, Surakarta City. The purpose of this study was to determine the influence of financial literacy, product innovation, and financial inclusion on the financial performance of culinary MSMEs in Alun-Alun Kidul, Surakarta City.This study uses quantitative data. The data source uses primary data. This study used a sample of 100 respondents with a sampling technique using purposive sampling. Data collection techniques used questionnaires, literature studies, and observations. Data analysis techniques used multiple linear regression analysis methods, t-tests, F-tests, and determination tests. The results of this study indicate that financial literacy does not significantly influence the financial performance of culinary MSMEs in Alun-alun Kidul, Surakarta City. Product innovation has a significant effect on the financial performance of culinary MSMEs in Alun-alun Kidul, Surakarta City. Financial inclusion does not significantly influence the financial performance of culinary MSMEs in Alun-alun Kidul, Surakarta City. The F-test results in this study showed a calculated F-value of 29.124 with a significance value (p-value) of 0.000 <0.05. Therefore, Ho is rejected and Ha is accepted. This means that the model used is appropriate for predicting the influence of the independent variables (financial literacy, product innovation, and financial inclusion) on the dependent variable (financial performance). The coefficient of determination (R²) for this model is 0.514 or 51.4%. This indicates that the independent variables X1 (financial literacy), X2 (product innovation), and X3 (financial inclusion) contribute 50% to Y (financial performance). The remaining 50% is explained by variables outside the model.